Nurturing the Fitrah: Managing the Integration of Montessori Pedagogy and Islamic Character Education - Ningsih, Ningsih; Malik, Amit Saepul; Supriyatna, Dede; Fundi, Venant (JURNAL AL-TANZIM, 2026)
This study aims to examine the integration of Montessori teaching methods with Islamic character development from an educational management perspective. The study emphasizes how the planning, organization, implementation, and supervision processes support the integration of Montessori pedagogy with Islamic values in early childhood education. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving teachers, students, parents, and school leaders. The research findings indicate that the Montessori approach aligns with children's developmental stages by promoting experiential learning, independence, and self-discipline, which align with the Islamic concept of fitrah (natural nature). Islamic values such as amanah (responsibility), istiqlal (independence), istiqamah (consistency), and ta'awun (cooperation) are systematically integrated through structured school management, classroom routines, teacher supervision, and collaborative partnerships with parents. Supporting factors include competent educators, a well-managed learning environment, and institutional commitment to values-based education. Challenges include the limited number of Montessori-trained teachers and diverse family backgrounds. This research suggests that integrating Montessori pedagogy and Islamic values enhances the quality of early childhood education by fostering student character and independence, strengthening collaboration between teachers and parents, and providing a foundation for policy development and teacher training in values-based education at the kindergarten level.